2016
DOI: 10.1557/adv.2016.360
|View full text |Cite
|
Sign up to set email alerts
|

Development of an all-SiC neuronal interface device

Abstract: The intracortical neural interface (INI) is a key component of brain machine interfaces (BMI) which offer the possibility to restore functions lost by patients due to severe trauma to the central or peripheral nervous system. Unfortunately today’s neural electrodes suffer from a variety of design flaws, mainly the use of non-biocompatible materials based on Si or W with polymer coatings to mask the underlying material. Silicon carbide (SiC) is a semiconductor that has been proven to be highly biocompatible, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Capacitance versus voltage measurements of Schottky contacts to the n + layer verified that the doping on the n + epi layer was on the order of 3.45 × 10 18 cm −3 which was consistent with our epi-doping estimates of ~3 × 10 18 cm −3 from prior growth runs using the same level of intentional nitrogen doping [ 38 ]. Typical doping of the p-type base epitaxial layer was ~1 × 10 16 cm −3 .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Capacitance versus voltage measurements of Schottky contacts to the n + layer verified that the doping on the n + epi layer was on the order of 3.45 × 10 18 cm −3 which was consistent with our epi-doping estimates of ~3 × 10 18 cm −3 from prior growth runs using the same level of intentional nitrogen doping [ 38 ]. Typical doping of the p-type base epitaxial layer was ~1 × 10 16 cm −3 .…”
Section: Resultssupporting
confidence: 86%
“…Five all-SiC electrodes of increasing geometrical surface area, via doubling electrode diameter from 25 to 800 µm (200 µm was left out to save real estate), were characterized electrochemically in PBS. Our previous investigation evaluated only 25 µm diameter electrodes and demonstrated capacitive interaction with little Faradaic activity [ 38 ]. That study demonstrated that 4H-SiC fits the same electrochemical model as reported for semiconductor electrodes [ 41 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Helium (He), with a flow rate of 700 sccm, was used as the carrier gas. The RF power was set to 200 W, substrate temperature to 300 °C, and pressure to 1100 mTorr [37,38]. Following photoresist patterning using AZ 15nXT-450 CPS negative photoresist (Microchemicals GmbH), a reactive ion etch (RIE; PlasmaTherm) was run for 210 s to open windows in the a -SiC film for the electrode sites.…”
Section: Methodsmentioning
confidence: 99%